Leunca (Solanum americanum Mill.): The uses as vegetable in two villages in Upper Citarum Area, Bandung, West Java, Indonesia - DEDE MULYANTO; JOHAN ISKANDAR; OEKAN S. ABDOELLAH; BUDIAWATI S. ISKANDAR; SELLY RIAWANTI; RUHYAT PARTASASMITA (Biodiversitas Journal of Biological Diversity, 2018)
Mulyanto D, Iskandar J, Abdoellah OS, Iskandar BS, Riawanti S, Partasasmita R. 2018. Leunca (Solanum americanum Mill.): The uses as vegetable in two villages in Upper Citarum Area, Bandung, West Java, Indonesia. Biodiversitas 19: 1941-1954. Leunca is known as botanical name as Solanum americanum Mill, Family of Solanaceae. In recent years, academic interest has been increasing. After so long studied as weeds, today leunca has also studied because of its important meaning as crop that has high nutritional and economic value in relation to food resilience of developing countries, as because of its chemical substances with its medicinal properties. Leunca was recorded in colonial period by botanists or agricultural scientists’ report as local vegetable in rural of West Java also in modern time by anthropologist or ecologists who studying rural population. In the recent time in Indonesia, leunca studies almost all have been focused on its pharmacological, agronomic, and economic aspects. The aspect that is related to Sundanese sociocultural system was almost neglected. This paper presents the finding of research on ethnobotany of leunca includes landraces, agronomical and utilization, traditional institutional aspect, and culinary culture food habits of leunca in rural Sundanese people. Method used in this study mixed-method of qualitative and quantitative was applied in this study, while some techniques including observation and semi-structured interviews were carried in the field research. The result of study showed that based on informants it has revealed that 7 kinds of plant that are named as leunca, however, only 3 kinds of leunca that are grown in their village. Among 7 kinds of leunca, leunca biasa (S. americanum) has been predominantly consumed both fruits and leaves. There is various food dishes are consumed fresh or cooked. Various dishes of leunca biasa have been culturally integrated everyday life of people and culturally as part of people identity of Sundanese people (urang Sunda). Other kinds of leunca, including leaves of leunca manuk (variety of S. americanum) have been consumed leunca as cooked vegetable, and its leaves have been used as traditional medicine of pet chicken disease.